Evaluate the clinical efficacy of Amrutadi tablet(Anubhut) as palliative care management in oral squamous cell carcinoma w.s.r to tobacco induced oral cancer -a single case study - Parmar, Damini Ben; Kumar Sharma, Rajesh; V Sangani, Vipulkumar; Padadhariya, Dhruval; Ninama, Divya Bahen (Asian Journal of Pharmaceutical Research and Development, 2023)
Aim: To Evaluate the clinical efficacy of Amrutadi tablet (Anubhuta)as palliative care management in oral squamous cell carcinoma. Background: The disease arbuda was prevalent during the Vedic period. In athar-vaveda2 there is reference of arbuda and its management. Arbuda is one of the surgical diseases and was explained in detailed by sushruta the pioneer of in ancient ayurvedic texts that have remarkable similarities with modern interpretation of cancer. Cancer is one of the most dreaded diseases of the 20th century and spreading further with continuance and increasing incidence in 21st century. Cancer is a disease caused by uncontrolled division of abnormal cells in any part of the body.More than 90% of cancer of the tobacco induced oral cancer are squamous cell carcinoma. Results and Discussion: A case of pain in oral cavity and mouth ulceration after biopsy and mri diagnosed as oral squamous cell carcinoma was given Amrutadi tablet for a period of 30 days. Symptom of pain in oral cavity mouth ulceration and associated symtoms dysphagia, anorexia has been improved moderately within a month. Assesement of patient has been done based on subjective and objective criteria before and after treatment, which shows improvement in patient condition.